The Scientific Landscape of the Aging-in-Place Literature: A Bibliometric Analysis - Saman Jamshidi; Seyedehnastaran Hashemi (Journal of Ageing and Longevity)
The world’s population is aging and, as populations age, they exhibit an increased prevalence of chronic diseases, which can reduce the independence of elderly individuals. The set of initiatives known as aging in place, a common policy response to the aging population, is preferred by both the elderly population and policymakers. Aging in place is a broad and multifaceted topic that involves multiple stakeholders and academic disciplines. A science map of the literature on aging in place can help researchers pinpoint their efforts and help policymakers make informed decisions. Thus, this study maps the scientific landscape of the aging-in-place literature. This review used bibliometric analysis to examine 3240 publications on aging in place indexed in the Web of Science. Using VOSviewer 1.6.20, it conducted various analyses, including a citation analysis and an analysis of the co-occurrence of author-provided keywords. The study identified key research areas, leading countries, institutions, and journals, central publications, and the temporal evolution of themes in the literature. Based on its keyword co-occurrence analysis, the study identified five major research-area clusters: (1) aging-in-place facilitators, (2) age-friendly communities, (3) housing, (4) assistive technologies, and (5) mental health. This study improves the understanding of the various interdisciplinary factors that have influenced the research on aging in place. By making this research more accessible, the study can help researchers and policymakers navigate the extensive information on aging in place and complex relationships more effectively.